Integrated Care model: Transition from acute to chronic care - Shahrzad Ghiyasvandian; Hooman Shahsavari; Pegah Matourypour; Mohamad Reza Golestannejad (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: Description and discussion dimensions of Integrated Care Model. Methods: A descriptive study is done that describe a technological innovation, intervention strategies for professional performance. Results: Integrated Care Model (ICM) has two main categories include individual and Group-and disease-specific Model. First, is used for risky patients or with comorbidities. In second category; Chronic Care Model (CCM) is common form of Integrated Care Model to improve resultants in the patients with chronic condition, to move from acute care to integrate, regular, long-lasting, preventative and community-based nursing. Final considerations: It is important to consider patient as an active member of the treatment team. It seems to be essential to monitor performance of care system. On the other hand, offer multidisciplinary care leads to present desirable care, tailored to the specific needs of patients regarding safety, patient-centered care and their culture.